2017
DOI: 10.3758/s13414-016-1268-3
|View full text |Cite
|
Sign up to set email alerts
|

Control blindness: Why people can make incorrect inferences about the intentions of others

Abstract: There is limited evidence regarding the accuracy of inferences about intention. The research described in this article shows how perceptual control theory (PCT) can provide a “ground truth” for these judgments. In a series of 3 studies, participants were asked to identify a person’s intention in a tracking task where the person’s true intention was to control the position of a knot connecting a pair of rubber bands. Most participants failed to correctly infer the person’s intention, instead inferring complex b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(5 citation statements)
references
References 34 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…This study replicated the earlier studies (Willett et al, 2017) showing the observers missed the controlled variables within a specific instructed task that they observed continuously, and this study extended the findings to a live observation. These studies support the case that most people do not immediately consider that behavior is a process of controlling perceived aspects of one’s body or environment when viewing someone else’s actions.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This study replicated the earlier studies (Willett et al, 2017) showing the observers missed the controlled variables within a specific instructed task that they observed continuously, and this study extended the findings to a live observation. These studies support the case that most people do not immediately consider that behavior is a process of controlling perceived aspects of one’s body or environment when viewing someone else’s actions.…”
Section: Discussionsupporting
confidence: 87%
“…All the actors in the study reported that they were indeed following the instructions. This study therefore challenges an alternative explanation for the findings of Willett et al (2017) that the actor in the video was actually following a different instruction from the one requiring control (“to keep the knot over the dot”), such as to “draw a mirror image.” Indeed, even though the actors in the current study wrote the word “hello”, our results would indicate that the actors were not controlling for this particular perceptual result of their action.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Yet observers can be mistaken in judging the nature of another person's behavior. One series of studies shows that a volunteer can be given a simple instruction (to keep a knot of a rubber band over a dot on a page while holding a pen) and yet over 90 percent of observers of this activity fail to correctly identify that this was the volunteer's instruction (Willett et al, 2017). This behavioral illusion occurs because observers notice the eyecatching features of a behavior, in this case drawing a shape on the page, and assume that what they have observed was intended or controlled.…”
Section: Mental Healthmentioning
confidence: 99%